Teaching Constraint Programming Using Fable-Based Learning - Chan, Mavis; Chun, Cecilia; Fung, Holly; Lee, Jimmy H.M.; Stuckey, Peter J. (Proceedings of the AAAI Conference on Artificial Intelligence, 2020)
The paper presents the pedagogical innovations and experience of the co-development of three MOOCs on the subject of “Modeling and Solving Discrete Optimization Problems” by two universities. In a nutshell, the MOOCs feature the Fable-Based Learning approach, which is a form of problem-based learning encapsulated in a coherent story plot. Each lecture video begins with an animation that tells a story following a novel. The protagonists of the story encounter a problem requiring technical assistance from the two professors from modern time via a magical tablet granted to them by a fairy god. The new pedagogy aims at increasing learners’ motivation and interests as well as situating the learners in a coherent learning context. In addition to scriptwriting, animation production and situating the teaching materials in the story plot, another challenge of the project is the remote distance between the two institutions as well as the need to produce all teaching materials in both (Mandarin) Chinese and English to cater for different geographic learning needs. The MOOCs have been running recurrently on Coursera since 2017. We present learner statistics and feedback, and discuss our experience with and preliminary observations of adopting the online materials in a Flipped Classroom setting.